Elasticity of Oral Tradition: Negotiating Cultural Identity and Linguistic Hybridity in Contemporary Indonesian Pantun - Enjel Trisnawati Banjarnahor (Winaya Inspirasi Nusantara Foundation, 2024)
The rapid expansion of globalization and digital networks within contemporary Indonesia has placed significant pressure on local oral traditions, forcing traditional communicative mediums to navigate intensive cultural flows and shifting modern sensibilities. Rather than sliding into obsolescence, traditional genres serve as active discursive sites where local communities renegotiate their socio-cultural identities. This study aims to investigate the structural and semantic transformations of contemporary Indonesian pantun to understand how cultural identity is discursively projected, maintained, and hybridized amidst modern globalizing forces. Employing a qualitative descriptive research design grounded in interpretive sociolinguistic inquiry, this study analyzed a purposively sampled corpus of 120 pantun stanzas collected from physical regional archives and digital repositories between 2018 and 2024. The findings demonstrate that while core cultural pillars, such as ancestral customs (adat), performing arts, culinary heritages, and religious philosophies, are systematically maintained through traditional metaphorical pairings, a significant portion of the corpus exhibits notable linguistic hybridity. Contemporary speakers smoothly incorporate global pop-culture tropes, modern socio-spatial environments, and foreign loanwords into the classical four-line, alternating rhyme matrix without fracturing its underlying structural or phonetic integrity. This dynamic illustrates that the strict boundaries of the genre act as an elastic creative canvas rather than an inflexible cage. Theoretically, these results challenge pessimistic narratives of cultural erosion by modeling the discursive resilience and glocalization of oral literature. Practically, the study implies that language pedagogy and heritage preservation frameworks must move away from rigid textual purism to support the living evolution of traditional arts in the digital age.